Genesis of the Dawadi potassium nitrate deposit in Lop Nor, China - Yu Zhang (Nature Portfolio, 2021)
Abstract Nitrate deposits are rare worldwide, especially potassium nitrate deposits; furthermore, their genesis remains disputed. There is a rare salt-lake type potassium nitrate deposit in the Dawadi area of Lop Nor at the eastern margin of the Tarim Basin, and the ore bodies show coexisting solid and liquid phases. Additionally, there are large sulphate-type potash deposits in the adjoining Luobei Depression, south of the Dawadi area. To determine why there are two different types of potash deposits in adjacent depressions with similar climates, field geological surveys were conducted and samples collected. It was found that the Tertiary clastic layer at the periphery of the Dawadi deposit was rich in high-salinity brine, with nitrate contents of up to 495–16,719 mg/L, much higher than those in the Luobei Depression, 1–35 mg/L. Additionally, a type of deep hydrothermal (Ca–Cl) brine was found in the fault zones, with nitrate contents of up to 8044 mg/L, dozens of times greater than that of ordinary groundwater. Using comprehensive analysis and research, we concluded that the Dawadi and Luobei depressions belong to different hydrological systems with no connection between them; thus, the two deposits belong to different metallogenic systems. Furthermore, groundwater played an important role in the mineralization of the potassium nitrate deposit, and a deep source may have been an important source of the ore-forming materials. The fault system widely developed in Lop Nor provides favorable channels for deep hydrothermal recharge, and the groundwater and deep hydrothermal brine could provide the source for the nitrate mineralization in the Dawadi Depression through water–rock reactions.